Analisis Penyelesaian Perbatasan Laut Antara Peru dengan Chili yang Diselesaikan Oleh Mahkamah Internasional (ICJ) - Dwi Imroatus Sholikah (CV Rewang Rencang, 2020)
The law of the sea is very instrumental in limiting the areas of sea, land, and waters of a country. The sea is a road that is very often used to connect one country with other countries for trade and even for the benefit of others. On the other hand, the existence of international sea law protects natural resources from being misused. The International Court of Justice resolves disputes between member states. It also provides opinions or advice to official bodies and specialized agencies established by the United Nations. In the performance of its duties, the International Court of Justice refers to international conventions to establish cases recognized by the states in dispute. The ICJ is also guided by international customs that are evidence of general practice.